Human pluripotent stem cells derived-cardiomyocytes (hPSC-CMs) to assess the impact of drug- and gene-induced changes on cell function - Mohd Yusof, Nurul Ain Nasim (2020)
The majority of data available for drug predictive safety and disease/polymorphism modelling are based on results from genetic association studies or from models other than humans, which can lead to conflicting mechanistic explanations. This thesis considers whether human pluripotent stem cell-derived cardiomyocytes (hPSC-CMs) could complement existing assays to improve drug safety screening and disease/polymorphism modelling by assessing the impact of drug- and gene-induced changes on cell function.